Debt and Conditionality under Endogenous Terms of Trade Adjustment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
The purpose of this study is to identify conditions under which renewed international lending will benefit both the developed and the developing countries. Our analysis will evaluate how the presence of terms of trade adjustment and distorted credit markets affect the conditions for the existence of beneficial lending. We demonstrate that in the presence of endogenous terms of trade adjustment, there are cases in which a competitive international banking system may not revitalize lending for investment purposes, even if such renewed lending is socially desirable. Renewed lending may require the appropriate conditionality, and the presence of endogenous terms of trade adjustment puts greater weight on investment conditionality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet